Financial Technology for Strengthening MSME Financial Management: A Systematic Literature Review (PRISMA) 2021-2025 - Kiki Anggraeny; Rischa Meiyani; Haryono Haryono; Maria Septijantini Alie (Penerbit Goodwood, 2026)
Purpose: This study aims to systematically examine the role of Financial Technology (FinTech) in strengthening financial management practices among Micro, Small, and Medium Enterprises (MSMEs), particularly in improving access to finance, cash flow management, and transparency.Research Methodology: This study adopts a Systematic Literature Review (SLR) approach based on the PRISMA protocol. Peer-reviewed journal articles published between 2021 and 2025 were retrieved from the Scopus database using predefined keywords related to FinTech, financial management and MSMEs. The selected studies were analyzed through content analysis to identify patterns, mechanisms, and research gaps in the adoption of FinTech and MSMES financial management.Results: The findings indicate that FinTech significantly enhances MSMES financial management through digital payment systems, digital lending platforms, accounting information systems, and data-driven financial tools. FinTech adoption improves transaction efficiency, the accuracy of financial records, access to alternative financing, and overall financial resilience. Financial and digital literacy are critical factors influencing successful FinTech utilization.Conclusions: FinTech serves as a strategic enabler of MSME financial management and business sustainability. Effective integration, supported by adequate literacy and regulatory support, enhances financial performance and resilience of the sector. Policymakers should promote inclusive fintech ecosystems.Limitations: This review was limited to English-language publications and cross-sectional studies, restricting insights into long-term effects.Contribution: This synthesis of recent evidence offers valuable insights for academics, policymakers, and practitioners in developing inclusive digital financial solutions.